Perfil populacional de pacientes com disartria atendidos em hospital terciário - Ribeiro, Ariella Fornachari (2009)
PURPOSE: To characterize the populational profile of dysarthric patients assisted in a tertiary hospital, and to present the most frequent speech disorders found in this population. METHODS: A specific protocol proposed for dysarthric patients was applied, gathering data through tasks that evaluate breathing, phonation, resonance, articulation, and prosody. Sixty protocols applied to patients evaluated at the Communication Disorders Ambulatory of the institution were the study took place were randomly selected for analysis. Data was descriptively analyzed. RESULTS: Regarding the populational profile of the dysarthric patients attended at a tertiary hospital, it was observed prevalence of male subjects, mostly aged from 20 to 50 years. The most common types of dysarthria were flaccid and unilateral upper motor neuron. Stroke was the most prevalent etiology for this speech disorder. Regarding the motor bases evaluated, it was observed a predominance of mixed breathing, hoarse voice, and normal velar movement, although mild hypernasality was identified. Articulation was mostly severely altered, and mild prosody alterations were predominant in the investigated population. CONCLUSION: It was possible to draw a profile of dysarthric patients assisted in a tertiary hospital in Brazil. The most common characteristics were: short breathing cycles, hoarse hypernasal phonation, moderate to severe articulation disorders, mild prosody impairment and low speech rate.